The Difficulties of English as a Foreign Language (EFL) Learners in Understanding Pragmatics - Fauzia Fauzia (Universitas Cokroaminoto Palopo, 2016)
Pragmatics is the study of the relation of signs to interpreters. For English foreign language (EFL) learners, the knowledge and comprehensible input of pragmatics is much needed. This paper is based on research project. The writer did the research survey by giving some respondents questionnaire. The respondent is some students from UAD, which is taken randomly. Besides using open questionnaire, the writer also got the data from in depth interview with some EFL learners, the native speaker who teaches English, and also did literature review from some books. The result of the research then gives some evidences that EFL learners difficulties in understanding the English pragmatics occurs in 1) greeting, 2) apologizing, 3) complimenting, and 4) thanking. The factors that promotes EFL learners’ difficulties in understanding because 1) the different culture and values between native speaker and learners; 2) habit that the usually use in their daily life.